ANALISIS FAKTOR YANG MEMPENGARUHI BOOK TAX GAP DAN PENGARUHNYA TERHADAP PERSISTENSI LABA - Persada, Aulia Eka; Martani, Dwi (UI Scholars Hub, 2010)
The aim of this study is to examine the factors affecting book tax gap and analyze the effects of book tax gap for the persistence of earnings using a panel data set of manufacturing company in Indonesia over the period 2001-2007. The key result suggests that, only tax loss utilization and the firm size significantly affect the book tax gap in Indonesia. The result for the persistence of earnings shows that both temporary and permanent book tax gap significantly affect the persistence of earnings. The result also shows there are other factors that affect the persistence of earnings like operating cash flows and accruals.